The Transcriptome of Human Endometrial Mesenchymal Stem Cells Under TGFβR Inhibition Reveals Improved Potential for Cell-Based Therapies - Gurung, Shanti; Williams, Sarah; Deane, James A.; Werkmeister, Jerome A.; Gargett, Caroline E. (Frontiers in Cell and Developmental Biology, 2018)
Mesenchymal stem/stromal cells (MSCs) are multipotent cells with favorable properties for cell therapies and regenerative medicine. Human endometrium harbors a small population of perivascular, clonogenic MSCs (eMSCs) identified by the SUSD2 marker. As for other MSCs, eMSCs require extensive in vitro expansion to generate clinically relevant numbers of cells, resulting in spontaneous differentiation, replicative senescence and cell death, decreasing therapeutic potency. We previously demonstrated that A83-01, a TGF-β receptor inhibitor, maintained eMSC clonogenicity, promoted proliferation, prevented apoptosis and maintained MSC function in vitro. Here we compare the transcriptome of passaged eMSCs from six women cultured with and without A83-01 for 7d. We identified 1206 differentially expressed genes (DEG) using a false discovery rate cut-off at 0.01 and fold change >2. Significant enrichment of genes involved in anti-inflammatory responses, angiogenesis, cell migration and proliferation, and collagen fibril and extracellular matrix organization were revealed. TGF-β, Wnt and Akt signaling pathways were decreased. Anti-fibrotic and anti-apoptotic genes were induced, and fibroblast proliferation and myofibroblast related genes were downregulated. We found increased MSC potency genes (TWIST1, TWIST2, JAG1, LIFR, and SLIT2) validating the enhanced potency of A83-01-treated eMSCs, and importantly no pluripotency gene expression. We also identified eMSCs’ potential for secreting exosomes, possibly explaining their paracrine properties. Angiogenic and cytokine protein arrays confirmed the angiogenic, anti-fibrotic and immunomodulatory phenotype of A83-01-treated eMSCs, and increased angiogenic activity was functionally demonstrated in vitro. eMSCs culture expanded with A83-01 have enhanced clinically relevant properties, suggesting their potential for cell-therapies and regenerative medicine applications.